Die Beziehungen deutscher und skandinavischer Orientalisten im Schatten des Nationalsozialismus: Von traditionellen Banden, weltanschaulichen Brüchen und (teils) getrennten Wegen nach 1945 - Malte Gasche (Studia Orientalia Electronica, 2016)
This article discusses the relationship between German and Scandinavian orientalists during the era of National Socialism. To begin with, the author examines the ideological and political interests that served to uphold oriental research in Nazi Germany. The article then continues with an inquiry into why Nazi German authorities were especially keen to maintain scientific relationships with Scandinavian orientalists during World War II. Traditionally, Scandinavian orientalists, many of whom had studied at German universities, tended to feel strongly connected with German Academia. Hence, the second part of the article considers the main reasons for the shift in attitude of Scandinavian scholars to Germany and underlines the turning points in the relationship, which, in most cases, led to an alienation from Germany and their German colleagues. In the third and last part of the article, the author looks into the impact of the National Socialistic era on the scientific orientation of Scandinavian orientalists after World War II. With regard to the international leading role of Scandinavian Assyriology, particular attention will be paid to the history of this sub-discipline. As far as research perspectives are concerned, the article not only suggests future research topics on the global history of oriental studies but also encourages comprehensive research on the history of Scandinavian universities in the shadow of the Third Reich.